KEPEMIMPINAN ADAPTIF KEPALA MADRASAH DALAM MENGHADAPI TRANSFORMASI PENDIDIKAN DI ERA DIGITAL - Umi Maghdhuroh; Arif Rumiyadi; Mukhammad Shobirin; Bambang Sumardjoko; Sri Lahir (STKIP Pesisir Selatan, 2026)
Educational transformation in the digital era requires madrasah principals to have adaptive skills in managing change and driving educational innovation. This study aims to analyze the adaptive leadership practices of madrasah principals in facing educational transformation in the digital era, identify the challenges faced, and examine the efforts made to overcome them. The study used a qualitative approach with a case study design at MI Muhammadiyah Al Manar Demak. Research informants consisted of madrasah principals, teachers, and education staff selected through purposive sampling and snowball sampling techniques. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model. Data validity was carried out through source triangulation, technical triangulation, member checking, and audit trails. The results showed that madrasah principals implemented adaptive leadership by strengthening digital vision, improving teacher competency, building a collaborative culture, and providing space for technology-based learning innovation. The main challenges faced included limited technological facilities, low digital literacy among some teachers, and resistance to change. To overcome these challenges, madrasah principals developed ongoing training, learning communities, and partnerships with various parties. The research findings confirm that adaptive leadership plays a crucial role in supporting digital transformation and improving the quality of education in madrasas.